The land of flowers - STILTON THEA; THEA STILTON (New York Scholastic Inc., 2016)
a fantasy adventure where the Thea Sisters travel to a magical realm to save the wilting "Seven Roses".
Keywords: the Netherlands, recognized worldwide as a leader in flower breeding; The moral lessons derived from such tales emphasize personal growth